2018
DOI: 10.1111/tmi.13171
|View full text |Cite
|
Sign up to set email alerts
|

Urban‐rural and sex differentials in tuberculosis mortality in Bangladesh: results from a population‐based survey

Abstract: Objective To assess tuberculosis mortality in Bangladesh through a population‐based survey using a Verbal Autopsy tool. Methods Nationwide mortality survey employing the WHO‐recommended Verbal Autopsy (VA) tool, and using InsilicoVA, a data‐driven method, to assign the cause of death. Using a three‐stage cluster sampling method, 3997 VA interviews were conducted in both urban and rural areas of Bangladesh. Cause‐specific mortality fractions (CSMF) were estimated using Bayesian probabilistic models. Results 6.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Encouragingly for patients, prices of essential antibiotics in private pharmacies in Bangladesh, including model stores, were not much higher than international prices in a recent study by , with only limited price increases between 2003 and 2019 44 . The increase in cases with dengue 21 , and the continued challenges with tuberculosis in Bangladesh, with patients typically seeking help from non-qualified practitioners before seeking help from qualified professionals, also needs addressing [45][46][47][48] . Encouragingly, whilst there are still cases of malaria in Bangladesh, co-ordinated activities have reduced these by more than 50% in 2016 versus 2010 49 .…”
mentioning
confidence: 99%
“…Encouragingly for patients, prices of essential antibiotics in private pharmacies in Bangladesh, including model stores, were not much higher than international prices in a recent study by , with only limited price increases between 2003 and 2019 44 . The increase in cases with dengue 21 , and the continued challenges with tuberculosis in Bangladesh, with patients typically seeking help from non-qualified practitioners before seeking help from qualified professionals, also needs addressing [45][46][47][48] . Encouragingly, whilst there are still cases of malaria in Bangladesh, co-ordinated activities have reduced these by more than 50% in 2016 versus 2010 49 .…”
mentioning
confidence: 99%
“…This finding was likely because both health and economic conditions are good in the cities in the study region, with few low-income groups. In contrast, in the study conducted in Bangladesh, regional differences in TB death rates were associated with a high prevalence of the disease in urban areas [ 29 ]. These urban areas had a high population density, with one-third of the residents living in slums, a scenario that is favourable for TB transmission [ 29 ].…”
Section: Discussionmentioning
confidence: 98%
“…Our findings support those of other studies, which reported different urban and rural epidemiological characteristics of elderly TB patients, however, there were inconsistencies between these studies in terms of the TB risk level. For example, in a study carried out in Bangladesh, the authors reported higher TB-related mortality rates in urban than rural regions [ 29 ]. Furthermore, results from Tanzania revealed significant differences in the epidemiological characteristics of TB in urban versus rural areas, with recurrent TB in rural but not urban regions [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…InterVA assumes that the symptoms are conditionally independent given a cause, an assumption that is likely reasonable for many symptoms but discards valuable information in particular cases that could be used to improve the overall performance of the model. (ii) InSilicoVA: is a probabilistic statistical tool that uses a hierarchical Bayesian framework to estimate the CoD for individuals and the population distribution [21,30]. InSilicoVA can be deployed where no access to the gold standard, and no labelled outcomes.…”
Section: Verbal Autopsy Modelsmentioning
confidence: 99%
“…However, the model requires a training dataset from a prior validation study [25]. Bayes rule PHRMC [8,18,21,26] HDSS [30] China and Tanzania [21] Philippines, Mexico, India [8,30], China [26] Hospital & Community Statistical Features [21,30] Hospital Statistical Narratives Features [8] ~9.4% (single cause) ~46.0% (multiple cause) (Adult) [26] 91% [21] 70% [8] ~18 (single cause) ~68% (multiple cause) (Adult) [26] 64% [30] Better [21] 68% [8] Less [26] Random Forest [8,21] Random Forest PHRMC China, Tanzania [21] Philippines, Mexico, Tanzania, India [8] Hospital & Community Statistical Features [21] Hospital Statistical & Narratives Features [8] 41% [21] 45% [8] 71% [21] 77% [8] Better [21] 68% [8] Symptom Pattern (SP) [27] Bayes 45.8% adults [26], 51.5% for children [26], and 32.5% for neonates [26] 74% [8] 0.710 for adults [26], 0.739 for children [26], and 0.751 for neonates [26] 68% [8] Less [26] SCI, CCC, CCVA, and PCVA.…”
Section: Verbal Autopsy Modelsmentioning
confidence: 99%